HOTS QUESTION PREPARATION TRAINING TO DEVELOP PEDAGOGIC SKILLS OF CHEMISTRY TEACHERS IN PALU CITY - Rahmawati, Sitti; Hamzah, Baharuddin; Afadil, Afadil; Dia Afrianti Sangkota, Vivi (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2023)
The ability to think highly abbreviated as HOTS is an ability applied in the revised 2013 Curriculum. Teachers are required to be able to make Higher Order Thinking Skills (HOTS)-oriented questions, which are questions whose questions can train students to think at a higher level at the level of analysis, evaluation, and creation. The provision of HOTS questions aims to create challenging learning for students to reflect and apply their reasoning. However, the reality in the field based on an interview with the head of the Palu City Chemistry MGMP, there are still many teachers who have not been able to make and compile HOTS questions, especially those who are members of the MGMP. Teachers who are members of the chemistry Subject Teacher Conference (MGMP) as partners of this service still experience problems in analyzing the forms of questions that can improve higher-order thinking skills (HOTS). To overcome this, training and mentoring with participatory models are carried out, which include: 1) analysis and interpretation of Bloom's taxonomy, 2) HOTS-based problem-making techniques, 3) characteristics and forms of HOTS questions, and analyzing question forms that can improve higher-order thinking skills (HOTS). The activity has been carried out well thanks to good cooperation with various parties. This is illustrated by the output in the form of HOTS questions that participants have made from the results of this training and service assistance. The final result of this service is according to the expected target, namely the existence of a book of HOTS questions produced which are used in chemistry learning.